1987
DOI: 10.1007/bf00218209
|View full text |Cite
|
Sign up to set email alerts
|

Osteonectin ? a differentiation marker of bone cells

Abstract: Bone matrix consists of type-I collagen and non-collagenous proteins. The latter represent only 10% of its total protein content. Since type-I collagen is also present in various other connective tissue sites (e.g., skin) it cannot be considered as bone specific. Among the non-collagenous components osteonectin--a 32 kilodalton (KD) glycoprotein linking mineral to collagen fibrils--is thought to be bone specific due to its biochemical properties. In the present study various skeletal and non-skeletal tissues w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
1
1

Year Published

1990
1990
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(60 citation statements)
references
References 18 publications
4
54
1
1
Order By: Relevance
“…This fact was demonstrated by immunolocalisation of low levels of ON to blood vessels and soft tissue. It has been reported from immunohistochemical studies that young osteocytes express ON (Jundt et al, 1987), but little immunolocalisation of ON to osteocytes was observed in this study with adult human bone. Although BSP and OPN were both immunolabelled with polyclonal antisera, anti-BSP demonstrated much weaker immunolabelling than anti-OPN, even though both proteins are structurally similar and contain the RGD domain.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…This fact was demonstrated by immunolocalisation of low levels of ON to blood vessels and soft tissue. It has been reported from immunohistochemical studies that young osteocytes express ON (Jundt et al, 1987), but little immunolocalisation of ON to osteocytes was observed in this study with adult human bone. Although BSP and OPN were both immunolabelled with polyclonal antisera, anti-BSP demonstrated much weaker immunolabelling than anti-OPN, even though both proteins are structurally similar and contain the RGD domain.…”
Section: Discussioncontrasting
confidence: 79%
“…Immunolocalisation of osteonectin (ON) (Jundt et al, 1987;Bianco et al, 1988;Park et al, 1996), alkaline phosphatase (ALP) (Bronckers et al, 1987), osteocalcin (OC) (Bronckers et al, 1987;Bronckers et al, 1994;Stafford et al, 1994;Semba et al, 2000;Rauch et al, 2000;Miao et al, 2001) bone sialoprotein (BSP) (Miao et al, 2001) and OC in situ hybridisation (Arai et al, 1993) were all performed in paraffin-embedded decalcified bone. The major disadvantage however of paraffin embedding as compared with plastic embedding is that it requires bone decalcification, a time-consuming process that eliminates essential information about mineralisation and locations of recent bone formation.…”
Section: Technovit 9100 New® Embeddingmentioning
confidence: 99%
“…Similar to TIMP RNA, alkaline phosphatase protein was found in more mature osteoblasts, as well as in preosteoblasts. Descriptions of the pattern of expression of other genes (osteopontin, osteonectin, osteocalcin) during osteogenesis suggests that hXBP-1 expression also correlates relatively well with that of osteonectin (SPARC) (Nomura et al, 1988;Holland et al, 1987;Metaranta et al, 1989; Mundlos et Jundt et al, 1987), except that this gene is expressed in hypertrophic chondrocytes, whereas hXBP-1 and TIMP are expressed principally in matrix secreting chondrocytes of the mature zone of the growth cartilage.…”
Section: Discussionmentioning
confidence: 99%
“…Osteonectin, a recently discovered non-collagenous protein in bone, is a phosphoprotein synthesized by osteoblasts, but it is not a specific bone protein (Termine 1983, Jundt et al 1987, Bianco et al 1988, Tracy et al 1988. Osteocalcin, or bone Gla protein, is vitamin K dependently synthesized by osteoblasts.…”
Section: Methodsmentioning
confidence: 99%